Little Ladybug - Berowska, Marta (Montreal, Canada : Tormont Publications Inc, 1996)
Little Ladybug is out and about when it starts to rain and thunder. If she doesn't hurry, the rain will wash away her spots.
Keywords: Bugs--Fiction; Childrens stories